Porosity and geometry control ductile to brittle deformation in indentation of porous solids. (15th June 2016) - Yadav, Shwetabh; Saldana, Christopher; Murthy, Tejas G.
Abstract: We report a series of plane strain wedge indentation experiments on a model porous brittle solid (soft rock) and study the effect of porosity and the indenter geometry on the mechanics of indentation. A series of images of the region surrounding the indenter were captured during indentation and were analysed using a particle image velocimetry algorithm. From the image analyses, deformation parameters were analysed as functions of porosity, including velocity fields and localization features such as compaction bands and fractures. The initiation of fracture during indentation was observed in the transition from brittle to ductile behaviour as a function of indentation depth. Higher ductility of the rock during indentation was observed for samples of high porosity and for indentation utilizing sharper wedges. The implications of these results for controlling deformation and fracture in rock drilling by tool geometry and rock porosity control are briefly discussed.